Introduction to parallel computing : from algorithms to programming on state-of-the-art platforms /: from algorithms to programming on state-of-the-art platforms. (2018) - Trobec, Roman; Slivnik, Boštjan; Bulić, Patricio; Robič, Borut, 1960-
No abstract available